The Influence of Good Corporate Governance and Profitability on Firm Value with Corporate Social Responsibility as a Mediating Variable - Diar Aprilliana Anggraeni; I Gusti Ketut Agung Ulupui; Rida Prihatni (Review of Ethics in Sustainable Finance and Accounting, 2025)
Publicly traded firms are now operating in an environment of growing intricacy, which has pushed issues like governance standards, societal obligations, and economic results to the center of their strategic planning conversations. The mining sector holds a distinctively prominent place in Indonesia because of its major contribution to the country’s economic performance, while simultaneously facing substantial environmental and social perils. Consequently, the deployment of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) represents a strategic imperative rather than a mere legal formality. Focusing on mining companies listed on the Indonesia Stock Exchange over the 2020–2024 timeframe, this study examines the effect of GCG and profitability on firm value, with CSR serving as a mediating factor. The study utilized a quantitative framework grounded in the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. According to the results, the meeting frequencies of both the board of directors and the board of commissioners have no significant bearing on either CSR or firm value. ROA, however, impacts both CSR and firm value. The influence of CSR on firm value is characterized by a negative trajectory. Furthermore, CSR does not mediate the effect of either board’s meeting frequency on firm value. Nevertheless, CSR does act as a mediator in the relationship between profitability and firm value, though the pathway it reveals is negative. These insights imply that profitability, relative to the Good Corporate Governance instruments considered in this study, emerges as the more dominant force shaping firm value.